Site assessment for industrial mass cultivation of microalgae: case studies from Persian Gulf and Oman Sea coastal areas - Abdolmajid Lababpour (تحقیقات کاربردی علوم جغرافیایی)
Providing enough microalgae biomass is required for various applications in sectors such as food, medicine and energy. The biomass resources such as land, water, nutrient and carbon dioxide are essential in cultivation feasibility study for biomass production as well as cost benefits. The aims of this research is therefore, site assessment and prioritization of potential site locations, carbon dioxide and water requirement for microalgae biomass production in the Persian Gulf and Oman Sea coastal areas. This analysis was undertaken to provide a preliminary assessment of the demands that may be expected on land, water, and CO2 resources in the Persian Gulf and Oman Sea coastal areas required for the large volume of biomass feedstock production by autotrophic microalgae. Emphasize was placed on the finding proper sites to achieve higher biomass productivity. The areas were selected to provide examples where geographical differences in water evaporation and solar resources, land availability profiles, water demand profiles and stationary CO2 sources would be possible alternatives for large scale production.